Perceived oral health among adults in Tehran, Iran; a telephone survey - Ghorbani, Zahra; Khoshnevisan, Mohammad Hossein; Ebn Ahmady, Arezoo (Journal of Dental School, 2020)
Objective: In comparison to clinical oral health indices, perceived oral health measures are less applied in large-scale epidemiological oral health studies in Iran. The aim of this study was to measure perceived oral health among adults in Tehran, Iran. Methods: In this cross-sectional study, perceived oral health was measured in 1100 adults in Tehran by two measures: 1- non-replaced extracted teeth, and 2- revised Rand dental health questions including pain, chewing problems and communication problems. Data was gathered by telephone interview using gender, age and level of education as socio-demographic information. Results: The mean number of non-replaced extracted teeth was 1.28 with 53.8% of adults reporting no extracted teeth. Extracted teeth was significantly less in younger (p<0.001) and more educated people (p<0.001). Rand dental health scores increased by age (p<0.001) but had no significant changes in different educational levels. The three items of Rand dental health were highly correlated (p<0.01) with Chronbach’s Alpha=0.73 but were not correlated with extracted teeth. Conclusion: Approximately half of Tehran adults have the experience of lacking one or more teeth, with a small group of them suffering from pain, chewing problems and communication problems.